COMBINED-FIELD FORMULATION FOR CONDUCTING BODIES WITH THIN COATINGS - Putnam, J. M. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A Galerkin method-of-moments (MM) formulation is developed for the problem of electromagnetic scattering from a conducting body with a thin coating. The formulation incorporates both the electric-field integral equation (EFIE) and magnetic-field integral equation (MFIE) formulations on the conductor and the dielectric surfaces. The formulation is developed in terms of generalized Galerkin matrix operators which allow for straightforward implementation into existing computer codes for coated bodies. The analysis allows a surface coating of nonuniform thickness that is characterized by complex permeability and permittivity; the analysis can be easily extended to the case of a thin multilayered body. Standard MM formulations for coated bodies, based on either the EFIE or the MFIE at the conductor surface, fail as the coating thickness approaches zero. The combined-field integral equation (CFIE) also fails in the limit of zero thickness. The present thin-coating formulation (TCF) wiU be shown to remain valid as the coating thickness approaches zero. In the limit, the matrix equation for the TCF reduces to a self- consistent set of equations for scattering from a conducting body, independent of the dielectric coating parameters. The TCF has been implemented for the case of scattering by a conducting body of revolution (BOR) with a thin dielectric layer. Examples are presented comparing the present formulation to other MM formulations. The TCF is demonstrated near internal resonant frequencies, and for some limiting cases for both bistatic and monostatic scattering. [Vol. 4, No. 2, pp. 15-26 (1989)]